Accurate transcription of simian virus 40 chromatin in a HeLa cell extract. - Brady, J N (1982)
During simian virus 40 viral maturation, a series of modifications occur which alter the composition of viral nucleoprotein complexes. As a consequence, the chromatin that is extracted from extracellular simian virus 40 virions exhibits properties that are similar to those of transcriptionally active eucaryotic chromatin. The influence of this chromatin structure on specific RNA initiation by RNA polymerase II was examined by using the in vitro HeLa cell extract of Manley et al. (Proc. Natl. Acad. Sci. U.S.A. 77:3855-3859, 1980). The 5' ends of RNA transcripts were positioned by the "run-off" assay, in which transcripts extend from the initiation site to termination sites created by restriction cleavage and by S1 nuclease analysis, using DNA probes labeled at their 5' termini. Two major early RNA transcripts, which originated at map positions 5,240 +/- 10 and 5,145 +/- 10, and two major late RNA transcripts, which originated at map positions 325 +/- 10 and 185 +/- 10, were identified. Transcripts were initiated with comparable relative efficiencies at the same 5' site when either purified DNA or chromatin was used as the template. Our results suggest that extracellular simian virus 40 virion chromatin modifications do not regulate simian virus 40 promoter selection but function to increase the accessibility of RNA promoter sequences to RNA polymerase II and allow efficient elongation of the RNA chain after the initiation event.